Սեպագիր մի քանի արձանագրությունների թարգմանության մասին - Վահան Գայսերյան (ՀՀ ԳԱԱ հրատ.)
Значительная часть клинописных надписей Ванского царства или их определенных частей до сих пор не имеет связанного перевода и остается непонятной. Основная часть слов этих надписей имеет убедительные индоевропейские параллели. The most part of cuneiform inscriptions of the Van kingdom or their certain parts have been remained incomprehensible till the present day: they have bad translation, that are formed without the hieroglyphs and are out of the standart construction.
Keywords: Auxiliary Sciences of History; Inscriptions; Epigraphy